Health and income poverty in Ireland, 2003 - 2006 - David Madden (University College Dublin, UCD School of Economics, 2008)
Recent advances in the measurement of bi-dimensional poverty are applied to a measure of poverty which incorporates income and health poverty. The correlation between income and poverty is examined using the Receiver Operating Characteristics curve. Following from this unidimensional and bi-dimensional poverty indices are calculated for Ireland for the years 2003-2006. Individual and bi-dimensional indices generally show a decline over the period with the biggest decline between 2003 and 2004. The results are generally not sensitive to the degree of poverty aversion or the substitutability between the different dimensions of poverty.
hdl:10197/758
Keywords: I12; I31; I32; 330; receiver operating characteristic; multidimensional poverty